2013
DOI: 10.1007/s00216-013-6736-1
|View full text |Cite
|
Sign up to set email alerts
|

Screening interaction between ochratoxin A and aptamers by fluorescence anisotropy approach

Abstract: By taking advantage of the intrinsic fluorescence of ochratoxin A (OTA), we present a fluorescence anisotropy approach for rapid analysis of the interactions between OTA and aptamers. The specific binding of OTA with a 36-mer aptamer can induce increased fluorescence anisotropy (FA) of OTA as the result of the freedom restriction of OTA and the increase of molecular volume, and the maximum FA change is about 0.160. This FA approach enables an easy way to investigate the effects of buffer compositions like meta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 41 publications
(52 citation statements)
references
References 27 publications
4
46
0
2
Order By: Relevance
“…Principle of detection of OTA using single fluorophore-labeled aptamer The applied 36-mer anti-OTA aptamers had good selectivity and displayed a K d about 50 nM in the binding buffer solution, as previously reported [21,23]. The binding affinity of the aptamer depended on the Ca 2+ or Mg 2+ , and proper ionic strength was also required for the high binding affinity [21,23].…”
Section: Resultsmentioning
confidence: 55%
See 4 more Smart Citations
“…Principle of detection of OTA using single fluorophore-labeled aptamer The applied 36-mer anti-OTA aptamers had good selectivity and displayed a K d about 50 nM in the binding buffer solution, as previously reported [21,23]. The binding affinity of the aptamer depended on the Ca 2+ or Mg 2+ , and proper ionic strength was also required for the high binding affinity [21,23].…”
Section: Resultsmentioning
confidence: 55%
“…The binding affinity of the aptamer depended on the Ca 2+ or Mg 2+ , and proper ionic strength was also required for the high binding affinity [21,23]. The previous study showed the optimized binding buffer solution contained 10 mM Tris-HCl (pH 8.5), 20 mM CaCl 2 , and 120 mM NaCl [21,23].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations